Neuropsychiatric symptoms in severe dementia: Associations with specific cognitive domains the Cache County Dementia Progression Study. (25th April 2019) - Rozum, William J.; Cooley, Bryce; Vernon, Elizabeth; Matyi, Joshua; Tschanz, JoAnn T.
Abstract : Objectives: To examine the prevalence of neuropsychiatric symptoms (NPS) and cognitive correlates in severe dementia. Methods: A population‐based sample of 56 individuals with severe dementia (85.7% Alzheimer's type; 67.9% female) were assessed with the Severe Cognitive Impairment Profile (SCIP) and the Neuropsychiatric Inventory (NPI). Descriptive statistics displayed the frequency of NPS and bivariate and multiple regression analyses examined the associations between cognitive domains on the SCIP and NPS total, domain, and cluster scores. Results: NPS were common in severe dementia with 98% of the sample exhibiting at least one symptom. Most common were delusions, apathy, agitation/aggression, and aberrant motor behavior, affecting 50% or more of participants. SCIP comportment was significantly associated with NPI total score and apathy ( r  = −.350 and −.292, respectively). All SCIP domains except for arithmetic, visuospatial, comportment, and motor behavior were significantly associated with agitation/aggression ( r  = −.285 to −.350). These associations remained in individual multiple regression models. Conclusion: In severe dementia, impairment in specific cognitive domains was associated with more severe NPS. Environmental manipulations to reduce processing demands in persons with severe dementia may be a useful strategy to target agitation and aggressive behaviors.